Preparation method of ECH cross-linked high-adsorption-performance lithium ion imprinted membrane

Through the ECH cross-linking method on the surface of Junye (PPY), 2- (hydroxyl) -12-crown 4-ether solves the problem of selective decline in the overlapping of traditional ion printing membrane materials, and achieves high-suction attachment. High -selective ionic seals are suitable for industrial lithium -lifting needs.

CN119346076APending Publication Date: 2025-01-24NORTHEAST DIANLI UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411468443.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-21
Publication Date
2025-01-24

Smart Images

  • Figure CN119346076A_ABST
    Figure CN119346076A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of an ECH cross-linked lithium ion imprinted membrane with high adsorption performance, and relates to the technical field of ion imprinting technology and electrochemical switch ion exchange. The invention aims to solve the problem that the selectivity is influenced by excessive crosslinking of the conventional ion-imprinted membrane material. The method comprises the following steps: 1, preparing an SP-PDA coated PVDF membrane; 2, preparation of a PPy / rGO conductive polymer; (3) preparing ECH-12C4 (Ethylenediamine); and 4, preparing the EIIP coated PVDF membrane. The preparation method is used for preparing the ECH cross-linked high-adsorption-performance lithium ion imprinted membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of ion imprinting technology and electrochemical switch ion exchange technology. Background Art

[0002] Lithium is known as an "energy metal". With the rapid development of electronic vehicles, electronic devices and electrochemical energy storage, the demand for lithium is increasing every year. Lithium reserves mainly exist in salt lake brine, seawater, geothermal water and lithium-containing ores, among which salt lake brine has the lowest cost for lithium extraction.

[0003] As one of the most common means of extracting lithium from salt lake brine, ion imprinting technology can accurately identify the target and combine with the adsorption target. This is mainly because ion imprinting technology is developed based on molecular imprinting technology. In actual salt lake brine, in addition to lithium ions, there are also a large number of other ions such as magnesium ions. Therefore, selective ion imprinting technology is very suitable for lithium extraction. Traditional ion imprinting materials rely on cross-linking agents to connect functional monomers with substrate materials during the preparation process, making the material rich in selective adsorption sites. However, there is an obvious disadvantage in this preparation process, that is, the uncontrollable reaction will cause the cross-linking agent to cross-link, thereby forming non-selective imprinting sites on the surface of the material, reducing the selectivity of the material. Therefore, it is very important to seek a more reasonable cross-linking method. Summary of the invention

[0004] The present invention aims to solve the problem that the existing traditional ion imprinted membrane materials have excessive cross-linking that affects the selectivity, and further provides a method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance.

[0005] A method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance is carried out according to the following steps:

[0006] 1. Preparation of SP-PDA@PVDF membrane:

[0007] Sodium periodate solution, sodium acetate buffer solution and dopamine hydrochloride are mixed to obtain a modified solution, and then the surfaces of both sides of the PVDF membrane are modified by shaking using the modified solution to obtain an SP-PDA@PVDF membrane;

[0008] 2. Preparation of PPy / rGO conductive polymer:

[0009] rGO was added to ethanol and stirred evenly, pyrrole was added and ultrasonicated, and then FeCl3 solution was added to react in an ice bath, and finally washed and dried to obtain PPy / rGO conductive polymer;

[0010] 3. Preparation of ECH-12C4:

[0011] 2-(Hydroxymethyl)-12-crown-4-ether and NaH are dissolved in DMF, and reacted in a closed nitrogen atmosphere at a temperature of 50°C to 65°C until the solution turns light brown, and then epichlorohydrin is added, and stirred in a closed nitrogen atmosphere at a temperature of 50°C to 65°C to obtain ECH-12C4;

[0012] The mass ratio of the volume of the 2-(hydroxymethyl)-12-crown 4-ether to NaH is 1 mL:(0.5-1) g; the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to DMF is 1:(500-1000); the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to epichlorohydrin is 1:(1-1.5);

[0013] 4. Preparation of EIIP@PVDF membrane:

[0014] The PPy / rGO conductive polymer is dispersed in deionized water and ultrasonically treated, and then ECH-12C4 and acetic acid are added, and stirred for 6h to 10h at a temperature of 50°C to 65°C and a rotation speed of 30r / min to 50r / min, and finally freeze-dried to obtain an ion-imprinted polymer, and the ion-imprinted polymer, SP-PDA@PVDF membrane and methanol are mixed, and then stirred for 6h to 8h at a temperature of 60°C to 65°C and a stirring speed of 30r / min to 50r / min to obtain an ECH cross-linked lithium ion imprinted membrane with high adsorption performance;

[0015] The mass ratio of the PPy / rGO conductive polymer to the volume ratio of ECH-12C4 is 1 g: (80-100) mL; the mass ratio of the PPy / rGO conductive polymer to the volume ratio of acetic acid is 1 g: (60-100) mL; the mass ratio of the ion-imprinted polymer to the area ratio of the SP-PDA@PVDF membrane is 1 g: (17-35) cm 2 .

[0016] The beneficial effects of the present invention are:

[0017] The present invention uses ECH as a cross-linking agent for the material, and relies on halogenation reaction to avoid excessive cross-linking to obtain an ion imprinted membrane with high adsorption capacity and high selectivity, thereby overcoming the disadvantage that excessive cross-linking leads to decreased selectivity of high adsorption materials, improving the separation performance of ion imprinted materials to meet the needs of industrial lithium extraction, and relying on electrochemical switch ion exchange technology to obtain ultra-high adsorption capacity.

[0018] 1. Compared with the conventional lithium ion adsorption and desorption process, the present invention only needs to adjust the applied potential, while the conventional ion imprinting process needs to rely on acid washing, so the present invention is more environmentally friendly and has good cyclic adsorption capacity;

[0019] 2. The present invention grafts functional monomers through halogenation reaction, which reduces the occurrence of over-grafting. This improves the selectivity of the ion-imprinted membrane, while maintaining a large adsorption capacity and having good adsorption performance;

[0020] 3. The present invention greatly accelerates the adsorption rate of lithium ions and reduces the influence of protonation through the action of an external electric field. It has a wider range of applications and is more compatible with the needs of industrial lithium extraction.

[0021] Instruction Manual

[0022] Figure 1 The schematic diagram of the ECH cross-linked lithium ion imprinted membrane with high adsorption performance prepared in Example 1;

[0023] Figure 2 Cyclic voltammograms of the Li-PPy@PVDF membrane prepared in comparative experiment 1, the SP-PDA@PVDF membrane prepared in step 1 of example 1, and the EIIP@PVDF membrane prepared in step 4;

[0024] Figure 3 The EIIP@PVDF membrane prepared in step 4 of Example 1 was subjected to different ion solutions (Mg 2+ , K + 、Na + Li + ) in the cyclic voltammetry curve;

[0025] Figure 4 A comparison chart of the selective adsorption performance of the IIP@PPy / rGO@PVDF membrane prepared in Experiment 2 and the EIIP@PVDF membrane prepared in Step 4 of Example 1;

[0026] Figure 5 The adsorption performance of the EIIP@PVDF membrane prepared in step 4 of Example 1 in a solution with a Mg / Li ion concentration ratio of 10 / 1;

[0027] Figure 6 The N2 adsorption-desorption curves of the Li-PPy@PVDF membrane prepared in the comparative experiment 1, the SP-PDA@PVDF membrane prepared in the step 1 of the example 1, and the EIIP@PVDF membrane prepared in the step 4 are shown;

[0028] Figure 7 The anti-protonation performance of the EIIP@PVDF membrane prepared in step 4 of Example 1;

[0029] Figure 8For scanning electron microscopy and surface element scanning, a is the surface of PVDF membrane, b is the surface of SP-PDA@PVDF membrane prepared in step one of Example 1, c is the surface of IIP@PPy / rGO@PVDF membrane prepared in comparative experiment 2, d is the surface of EIIP@PVDF membrane prepared in step four of Example 1, e is the cross section of IIP@PPy / rGO@PVDF membrane prepared in comparative experiment 2, f is the cross section of EIIP@PVDF membrane prepared in step four of Example 1, g is the C element distribution map of the surface of EIIP@PVDF membrane prepared in step four of Example 1, h is the N element distribution map of the surface of EIIP@PVDF membrane prepared in step four of Example 1, and i is the O element distribution map of the surface of EIIP@PVDF membrane prepared in step four of Example 1;

[0030] Fig. 9 The relationship between the adsorption capacity and adsorption time of the EIIP@PVDF membrane prepared in step 4 of Example 1. Figure a shows the relationship between the adsorption capacity and adsorption time of the membrane when a voltage of 1.2 V is applied, and Figure b shows the relationship between the adsorption capacity and adsorption time of the membrane when no voltage is applied;

[0031] Fig.10 This is the narrow track XPS scan of Li for the EIIP@PVDF membrane prepared in step 4 of Example 1 after applying reduction potential and oxidation potential. DETAILED DESCRIPTION

[0032] Specific implementation method 1: This implementation method is a method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance, which is carried out according to the following steps:

[0033] 1. Preparation of SP-PDA@PVDF membrane:

[0034] Sodium periodate solution, sodium acetate buffer solution and dopamine hydrochloride are mixed to obtain a modified solution, and then the surfaces of both sides of the PVDF membrane are modified by shaking using the modified solution to obtain an SP-PDA@PVDF membrane;

[0035] 2. Preparation of PPy / rGO conductive polymer:

[0036] rGO was added to ethanol and stirred evenly, pyrrole was added and ultrasonicated, and then FeCl3 solution was added to react in an ice bath, and finally washed and dried to obtain PPy / rGO conductive polymer;

[0037] 3. Preparation of ECH-12C4:

[0038] 2-(Hydroxymethyl)-12-crown-4-ether and NaH are dissolved in DMF, and reacted in a closed nitrogen atmosphere at a temperature of 50°C to 65°C until the solution turns light brown, and then epichlorohydrin is added, and stirred in a closed nitrogen atmosphere at a temperature of 50°C to 65°C to obtain ECH-12C4;

[0039] The mass ratio of the volume of the 2-(hydroxymethyl)-12-crown 4-ether to NaH is 1 mL:(0.5-1) g; the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to DMF is 1:(500-1000); the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to epichlorohydrin is 1:(1-1.5);

[0040] 4. Preparation of EIIP@PVDF membrane:

[0041] The PPy / rGO conductive polymer is dispersed in deionized water and ultrasonically treated, and then ECH-12C4 and acetic acid are added, and stirred for 6h to 10h at a temperature of 50°C to 65°C and a rotation speed of 30r / min to 50r / min, and finally freeze-dried to obtain an ion-imprinted polymer, and the ion-imprinted polymer, SP-PDA@PVDF membrane and methanol are mixed, and then stirred for 6h to 8h at a temperature of 60°C to 65°C and a stirring speed of 30r / min to 50r / min to obtain an ECH cross-linked lithium ion imprinted membrane with high adsorption performance;

[0042] The mass ratio of the PPy / rGO conductive polymer to the volume ratio of ECH-12C4 is 1 g: (80-100) mL; the mass ratio of the PPy / rGO conductive polymer to the volume ratio of acetic acid is 1 g: (60-100) mL; the mass ratio of the ion-imprinted polymer to the area ratio of the SP-PDA@PVDF membrane is 1 g: (17-35) cm 2 .

[0043] Principle: 2-(Hydroxymethyl)-12-crown 4-ether (2H12C4) is used as the functional monomer, and 2H12C4 is fixed on the surface of polypyrrole (PPy) through the halogenation reaction of epichlorohydrin (ECH). The covalent bond reaction grafting method is used to maintain a rich three-dimensional network pore structure, providing an effective channel for ion transport. Compared with the traditional cross-linking agent grafting method, this method effectively avoids excessive cross-linking and effectively improves the selectivity of the material. The material prepared by this method has lower resistance and reduces circuit loss during transportation. Driven by an external electric field, the ions in the solution are transported to the pores of the membrane electrode material, and the membrane electrode can effectively increase the bonding between 2H12C4 and Li + The complexing force is more conducive to increasing the adsorption capacity.

[0044] The beneficial effects of this embodiment are:

[0045] This embodiment uses ECH as a cross-linking agent for the material, and relies on halogenation reaction to avoid excessive cross-linking to obtain an ion imprinted membrane with high adsorption capacity and high selectivity, overcomes the disadvantage of excessive cross-linking leading to decreased selectivity of high adsorption materials, improves the separation performance of ion imprinted materials to meet the needs of industrial lithium extraction, and relies on electrochemical switching ion exchange technology to obtain ultra-high adsorption capacity.

[0046] 1. Compared with the conventional lithium ion adsorption and desorption process, this embodiment only needs to adjust the applied potential, while the conventional ion imprinting process needs to rely on acid washing, so the present invention is more environmentally friendly and has good cyclic adsorption capacity;

[0047] 2. This embodiment uses halogenation reaction to graft polymerize the functional monomers, which reduces the occurrence of over-grafting. This improves the selectivity of the ion-imprinted membrane, while maintaining a large adsorption capacity and having good adsorption performance;

[0048] 3. This implementation method greatly accelerates the adsorption rate of lithium ions and reduces the influence of protonation through the effect of an external electric field. It has a wider range of applications and is more compatible with the needs of industrial lithium extraction.

[0049] Specific embodiment 2: This embodiment is different from specific embodiment 1 in that the modified solution described in step 1 is prepared by mixing sodium periodate solution and sodium acetate buffer solution, and then adding dopamine hydrochloride to dissolve to obtain a modified solution. Others are the same as specific embodiment 1.

[0050] Specific implementation method three: This implementation method is different from specific implementation method one or two in that: the volume ratio of the sodium periodate solution to the sodium acetate buffer solution described in step one is 1:(4-5); the mass ratio of the volume of the sodium periodate solution described in step one to dopamine hydrochloride is 1mL:(0.01-0.02)g; the concentration of the sodium periodate solution described in step one is 20mM-30mM; the concentration of the sodium acetate buffer solution described in step one is 50mM-70mM, and the pH is 4-5. Others are the same as specific implementation method one or two.

[0051] Specific embodiment 4: This embodiment differs from the specific embodiments 1 to 3 in that: in step 1, the surfaces of both sides of the PVDF membrane are modified by vibration using a modified solution, specifically according to the following steps:

[0052] ① Place the PVDF membrane on the surface of the modified solution, so that one side of the PVDF membrane contacts the modified solution and the other side contacts the air, and then oscillate for 6h to 7h at room temperature and an oscillation speed of 120r / min to 150r / min to obtain a PVDF membrane with one side modified;

[0053] ② Replace the modification solution and repeat step ① to treat the other side of the modified PVDF membrane, and finally wash and dry to obtain the SP-PDA@PVDF membrane. The rest is the same as the specific embodiments 1 to 3.

[0054] Specific embodiment 5: This embodiment differs from specific embodiments 1 to 4 in that the pore size of the PVDF membrane in step 1 is 0.22 μm to 0.45 μm, and the thickness is 125 μm to 150 μm. Other aspects are the same as specific embodiments 1 to 4.

[0055] Specific embodiment 6: This embodiment is different from specific embodiments 1 to 5 in that: the volume ratio of the mass of rGO described in step 2 to ethanol is 1g: (100-200) mL; the volume ratio of the mass of rGO described in step 2 to pyrrole is 1g: (2-4) mL; the volume ratio of the mass of rGO described in step 2 to FeCl3 solution is 1g: (30.3-35) mL; the concentration of the FeCl3 solution described in step 2 is 1mol / L-2mol / L. Others are the same as specific embodiments 1 to 5.

[0056] Specific embodiment 7: This embodiment is different from specific embodiments 1 to 6 in that: in step 2, rGO is added to ethanol, and stirred for 30 to 60 minutes at a rotation speed of 20 r / min to 50 r / min, pyrrole is added, and ultrasonic treatment is performed for 5 to 10 minutes at an ultrasonic power of 100 W to 120 W, and then FeCl3 solution is added, and the reaction is carried out in an ice bath at a temperature of -5°C to 0°C for 6 hours to 8 hours, and finally washed with HCl at a concentration of 1 mol / L to 2 mol / L and dried to obtain PPy / rGO conductive polymer. The rest is the same as specific embodiments 1 to 6.

[0057] Specific embodiment eight: This embodiment differs from specific embodiments one to seven in that: in step three, the reaction is carried out for 6 to 10 hours under the conditions of a closed nitrogen atmosphere and a temperature of 50°C to 65°C, the solution turns light brown, and then epichlorohydrin is added, and stirred for 48 to 72 hours under the conditions of a closed nitrogen atmosphere, a temperature of 50°C to 65°C, and a rotation speed of 30 r / min to 50 r / min. The rest is the same as specific embodiments one to seven.

[0058] Specific embodiment 9: This embodiment is different from specific embodiments 1 to 8 in that: the volume ratio of the mass of the PPy / rGO conductive polymer described in step 4 to deionized water is 1g:(100-150)mL; the volume ratio of the mass of the ion-imprinted polymer described in step 4 to methanol is 1g:(180-200)mL. Others are the same as specific embodiments 1 to 8.

[0059] Specific embodiment 10: This embodiment differs from Specific embodiments 1 to 9 in that: the ultrasonic treatment described in step 4 is specifically carried out at a power of 50W to 120W for 5min to 25min; the freeze drying described in step 4 is specifically carried out at a temperature of -40°C to 2°C for 12h to 18h. The rest is the same as Specific embodiments 1 to 9.

[0060] The following examples are used to verify the beneficial effects of the present invention:

[0061] Embodiment 1:

[0062] A method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance is carried out according to the following steps:

[0063] 1. Preparation of SP-PDA@PVDF membrane:

[0064] Sodium periodate solution (20 mM, 20 mL) and sodium acetate buffer solution (50 mM, pH = 5.0, 80 mL) were mixed, and then dopamine hydrochloride (0.2 g) was added to dissolve to obtain a modified solution, and then the surfaces of both sides of the PVDF membrane were oscillated and modified using the modified solution to obtain an SP-PDA@PVDF membrane;

[0065] 2. Preparation of PPy / rGO conductive polymer:

[0066] 0.5 grGO was added to 50 mL ethanol and stirred for 30 min at a speed of 30 r / min, then 1 mL pyrrole was added and ultrasonic treatment was performed for 5 min at an ultrasonic power of 120 W, then 15.15 mL FeCl3 solution (1 mol / L) was added, and the mixture was reacted for 8 h in an ice bath at -5 °C, and finally washed with 1 mol / L HCl and dried to obtain a PPy / rGO conductive polymer;

[0067] 3. Preparation of ECH-12C4:

[0068] 0.1 mL of 2-(hydroxymethyl)-12-crown-4-ether and 0.05 g of NaH were dissolved in 100 mL of DMF, and the mixture was reacted for 8 h at 50 °C in a closed nitrogen atmosphere until the solution turned light brown. Then, 0.1 mL of epichlorohydrin was added, and the mixture was stirred for 72 h at 50 °C and 30 r / min in a closed nitrogen atmosphere to obtain ECH-12C4.

[0069] 4. Preparation of EIIP@PVDF membrane:

[0070] 0.5g PPy / rGO conductive polymer was dispersed in 50mL deionized water and ultrasonicated for 15min at a power of 120W, then 40.15mL ECH-12C4 and 30mL acetic acid were added, stirred for 8h at a temperature of 65℃ and a speed of 30r / min, and finally freeze-dried for 18h at a temperature of -30℃ to obtain ion-imprinted polymer, 0.5g ion-imprinted polymer, SP-PDA@PVDF membrane (cut into four uniform sectors) and 90mL methanol were mixed, and then stirred for 8h at a temperature of 65℃ and a stirring speed of 30r / min to obtain ECH cross-linked lithium ion imprinted membrane with high adsorption performance, namely EIIP@PVDF membrane;

[0071] In step 1, the surfaces of both sides of the PVDF membrane are modified by vibration using a modified solution, specifically by the following steps:

[0072] ① Place a PVDF membrane (pore size 0.45 μm, thickness 125 μm, diameter 47 mm) on the surface of the modified solution, so that one side of the PVDF membrane contacts the modified solution and the other side contacts the air, and then oscillate for 6 hours at room temperature (25°C) and an oscillation speed of 130 r / min, and keep the PVDF membrane in contact with the modified solution and the air at one side during the oscillation process. After the oscillation is completed, a PVDF membrane with one side modified is obtained;

[0073] ② Replace the modification solution and repeat step ① to treat the other side of the modified PVDF membrane, and finally wash and dry to obtain the SP-PDA@PVDF membrane; both sides of the SP-PDA@PVDF membrane are dark.

[0074] Comparative Experiment 1: This comparative experiment is different from Example 1 in that the rGO in step 2 is replaced by SP-PDA@PVDF membrane, and in step 2, the SP-PDA@PVDF membrane (cut into four uniform sectors) is added to 50 mL of ethanol and stirred for 30 min at a speed of 30 r / min, and then 1 mL of pyrrole is added, and ultrasonic treatment is performed for 5 min at an ultrasonic power of 120 W, and then 15.15 mL of FeCl3 solution (1 mol / L) is added, and the reaction is carried out in an ice bath at a temperature of -5°C for 8 h, and finally washed with 1 mol / L HCl and dried. Dry to obtain PPy@PVDF membrane; omit step 3; in step 4, add PPy@PVDF membrane to 50mL deionized water, then add 40.15mL ECH-12C4 and 30mL acetic acid, stir for 8h at 65℃ and 30r / min, finally freeze-dry for 18h at -30℃ to obtain treated PPy@PVDF membrane, mix the treated PPy@PVDF membrane with 90mL methanol, then stir for 8h at 65℃ and 30r / min to obtain Li-PPy@PVDF membrane. The rest is the same as in Example 1.

[0075] Comparative experiment 2: The difference between this comparative experiment and Example 1 is that step 3 is omitted; in step 4, 0.2g PPy / rGO conductive polymer and 80mL anhydrous methanol are mixed, ultrasonicated for 5min at a power of 120W, then 0.1mL ethylene glycol dimethacrylate (EGDMA) is added, reacted for 8h at a temperature of 65°C and a speed of 30r / min, and then SP-PDA@PVDF membrane, 0.05mL benzo-12-crown 4-ether (B12C4), 0.1mL ethylene glycol dimethacrylate (EGDMA) and 0.02g azobisisobutyronitrile (AIBN) are added, and finally condensed and refluxed for 24h at a temperature of 75°C to obtain IIP@PPy / rGO@PVDF membrane. The rest is the same as Example 1.

[0076] Figure 1 The schematic diagram of the ECH cross-linked lithium ion imprinted membrane with high adsorption performance prepared in Example 1; Figure 1 As shown in (left), PPy grows in situ on the rGO surface and combines by π-π interaction. Relying on the large specific surface area and good conductivity of rGO, the loading amount of PPy is increased, providing more grafting sites for the grafting of functional monomers. ECH-12C4 is mainly connected with PPy, relying on the halogenation reaction between the active hydrogen in the NH bond on PPy and the chlorine at the end of ECH to achieve the grafting and crosslinking of functional monomers, avoiding the formation of invalid imprinting sites by the crosslinker, thereby reducing the selectivity of the material; secondly, the adsorption process of lithium ions, such as Figure 1As shown in (middle), after applying a reduction potential (connected to the negative electrode of the power supply), lithium ions are adsorbed by the crown ether by the action of the electric field force, realizing the extraction of lithium ions; the desorption process of lithium ions is shown in Figure 1 As shown in (right), after applying an oxidation potential (connected to the positive electrode of a power source), PPy has the characteristic of showing positive charge when oxidized as an anode, and lithium ions are desorbed by relying on the charge balance effect.

[0077] Figure 2 The cyclic voltammetry curves of the Li-PPy@PVDF membrane prepared in the comparative experiment 1, the SP-PDA@PVDF membrane prepared in the step 1 of the embodiment 1, and the EIIP@PVDF membrane prepared in the step 4 are shown; as the area enclosed by the rGO and PPy loading curves increases, it indicates that the loading of rGO and PPy significantly improves the conductivity and capacitance of the membrane, reduces the resistance of the membrane, and increases the specific capacitance of the membrane. At the same time, after using covalent cross-linking, the cyclic voltammetry curves do not change significantly, indicating that the covalent cross-linking method will not affect the conductivity and specific capacitance of the membrane.

[0078] Figure 3 The EIIP@PVDF membrane prepared in step 4 of Example 1 was subjected to different ion solutions (Mg 2+ , K + 、Na + Li + ) in the cyclic voltammetry curve; it can be seen from the figure that the redox peak exists only in the lithium ion solution, indicating that the membrane has good selectivity for lithium ions.

[0079] Li, Na, K and Mg ions were mixed, and the concentration of each ion in the mixed solution was 200 mg / L, the pH of the mixed solution was 7, and then the selective adsorption performance test was performed; and the selectivity coefficient was specifically calculated according to the following formula:

[0080] K d =(C0-C e )V / (mC e ) (1)

[0081]

[0082] Where C0 represents the initial concentration of the solution (mg / L), C e represents the concentration of the solution after adsorption (mg / L), V represents the volume of the solution (mg), m represents the mass of the membrane (mg), α is the selectivity coefficient, M e Mainly Na + , K + Mg 2+ .

[0083] Figure 4The following is a comparison chart of the selective adsorption performance of the IIP@PPy / rGO@PVDF membrane prepared in comparative experiment 2 and the EIIP@PVDF membrane prepared in step 4 of Example 1; it can be seen that the membrane has a significant decrease in the adsorption of Na, K and Mg ions, while the lithium ion adsorption performance still maintains a level comparable to that of the organic cross-linking method, with the two cross-linking methods having lithium adsorption amounts of 193 mg / g (comparative experiment 2) and 178 mg / g (example 1). In the process of extracting lithium from salt lake brine, there are mainly interferences from Na, K and Mg ions. The competitive relationship between these ions and Li ions will cause the membrane's ability to adsorb lithium ions to decrease. The selectivity coefficient is usually used to represent the influence of the membrane on the ion. The larger the selectivity coefficient, the smaller the influence of the ion on the membrane's adsorption of lithium ions, and the stronger the membrane's ability to selectively adsorb lithium in salt lake brine. The Na, K and Mg selectivity coefficients of the EIIP@PVDF membrane prepared in step 4 of Example 1 are 11.38, 11.38 and 4.78, while the Na, K and Mg selectivity coefficients of the IIP@PPy / rGO@PVDF membrane prepared in comparison experiment 2 are 5.47, 8.67 and 4, respectively; this indicates that the covalent cross-linking method in Example 1 effectively improves the membrane's selectivity for lithium ion adsorption.

[0084] Prepare a solution with a Mg / Li ion concentration ratio of 10 / 1 (pH 7), wherein the lithium ion concentration is 200 mg / L and the magnesium ion concentration is 2000 mg / L; Figure 5 The adsorption performance of the EIIP@PVDF membrane prepared in step 4 of Example 1 in a solution with a Mg / Li ion concentration ratio of 10 / 1 is shown; the results show that the high magnesium-to-lithium ratio has no effect on the adsorption performance of the membrane, and the membrane's adsorption of lithium is 210 mg / g, which basically maintains the original level.

[0085] Figure 6 The N2 adsorption-desorption curves of the Li-PPy@PVDF membrane prepared in Experiment 1, the SP-PDA@PVDF membrane prepared in Step 1 of Example 1, and the EIIP@PVDF membrane prepared in Step 4 are compared. As can be seen from the figure, the EIIP@PVDF membrane prepared in Example 1 has the largest specific surface area, which is 27m 2 / g, while the specific surface areas of Li-PPy@PVDF membrane and SP-PDA@PVDF membrane are 21m 2 / g and 22m 2 / g.

[0086] Figure 7The anti-protonation performance of the EIIP@PVDF membrane prepared in step 4 of Example 1; as can be seen from the figure, the adsorption capacity can still reach 98 mg / g when the pH is equal to 1, and the surface membrane has good anti-protonation performance. The adsorption amount is 214 mg / g when the pH is 7, and the adsorption amount is 109 mg / g when the pH is 10, indicating that the membrane still has a large adsorption capacity under alkaline conditions. In summary, the membrane has a wide pH value application range.

[0087] Figure 8 For scanning electron microscopy and surface element scanning, a is the surface of PVDF membrane, b is the surface of SP-PDA@PVDF membrane prepared in step one of Example 1, c is the surface of IIP@PPy / rGO@PVDF membrane prepared in comparative experiment 2, d is the surface of EIIP@PVDF membrane prepared in step four of Example 1, e is the cross-section of IIP@PPy / rGO@PVDF membrane prepared in comparative experiment 2, f is the cross-section of EIIP@PVDF membrane prepared in step four of Example 1, g is the C element distribution diagram of the surface of EIIP@PVDF membrane prepared in step four of Example 1, h is the N element distribution diagram of the surface of EIIP@PVDF membrane prepared in step four of Example 1, i is the O element distribution diagram of the surface of EIIP@PVDF membrane prepared in step four of Example 1; it can be seen that the membrane prepared by the covalent cross-linking method has a porous structure, while the membrane prepared by the organic cross-linking method has a large amount of deposition on the surface, indicating that the covalent cross-linking method can improve excessive cross-linking, and the C, N, and O elements on the membrane surface are evenly distributed on the membrane surface, indicating that the material is successfully loaded on the membrane.

[0088] Fig. 9 Figure 1 shows the relationship between the adsorption capacity and adsorption time of the EIIP@PVDF membrane prepared in step 4 of Example 1. Figure a shows the relationship between the adsorption capacity and adsorption time of the membrane under an applied voltage of 1.2 V, and Figure b shows the relationship between the adsorption capacity and adsorption time of the membrane without an applied voltage. It can be seen from the original data curve that when a voltage of 1.2 V is applied, the adsorption capacity of the membrane can reach 214 mg.g in 30 min. -1 Without applying voltage, the membrane needs 600 min to reach an adsorption capacity of 98 mg.g -1 This indicates that the existence of an external electric field greatly accelerates the adsorption rate of the membrane.

[0089] Fig.10 Narrow track XPS scan of Li for the EIIP@PVDF membrane prepared in step 4 of Example 1 after applying reduction potential and oxidation potential; as can be seen from the figure, the peak of Li appears after applying the reduction potential, and the peak of Li disappears after applying the oxidation potential, indicating that the membrane achieves lithium adsorption and desorption by relying on the redox potential.

Claims

1. A method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance, characterized in that It is carried out in the following steps:

1. Preparation of SP-PDA@PVDF membrane: Sodium periodate solution, sodium acetate buffer solution and dopamine hydrochloride are mixed to obtain a modified solution, and then the surfaces of both sides of the PVDF membrane are modified by shaking using the modified solution to obtain an SP-PDA@PVDF membrane; 2. Preparation of PPy / rGO conductive polymer: rGO was added to ethanol and stirred evenly, pyrrole was added and ultrasonicated, and then FeCl3 solution was added to react in an ice bath, and finally washed and dried to obtain PPy / rGO conductive polymer; 3. Preparation of ECH-12C4: 2-(Hydroxymethyl)-12-crown-4-ether and NaH are dissolved in DMF, and reacted in a closed nitrogen atmosphere at a temperature of 50°C to 65°C until the solution turns light brown, and then epichlorohydrin is added, and stirred in a closed nitrogen atmosphere at a temperature of 50°C to 65°C to obtain ECH-12C4; The mass ratio of the volume of the 2-(hydroxymethyl)-12-crown 4-ether to NaH is 1 mL:(0.5-1) g; the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to DMF is 1:(500-1000); the volume ratio of the 2-(hydroxymethyl)-12-crown 4-ether to epichlorohydrin is 1:(1-1.5); 4. Preparation of EIIP@PVDF membrane: The PPy / rGO conductive polymer is dispersed in deionized water and ultrasonically treated, and then ECH-12C4 and acetic acid are added, and stirred for 6h to 10h at a temperature of 50°C to 65°C and a rotation speed of 30r / min to 50r / min, and finally freeze-dried to obtain an ion-imprinted polymer, and the ion-imprinted polymer, SP-PDA@PVDF membrane and methanol are mixed, and then stirred for 6h to 8h at a temperature of 60°C to 65°C and a stirring speed of 30r / min to 50r / min to obtain an ECH cross-linked lithium ion imprinted membrane with high adsorption performance; The mass ratio of the PPy / rGO conductive polymer to the volume ratio of ECH-12C4 is 1 g: (80-100) mL; the mass ratio of the PPy / rGO conductive polymer to the volume ratio of acetic acid is 1 g: (60-100) mL; the mass ratio of the ion-imprinted polymer to the area ratio of the SP-PDA@PVDF membrane is 1 g: (17-35) cm 2 .

2. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that The modified solution described in step 1 is specifically prepared according to the following steps: sodium periodate solution and sodium acetate buffer solution are mixed, and then dopamine hydrochloride is added to dissolve to obtain a modified solution.

3. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that The volume ratio of the sodium periodate solution described in step one to the sodium acetate buffer solution is 1:(4-5); the mass ratio of the volume of the sodium periodate solution described in step one to dopamine hydrochloride is 1 mL:(0.01-0.02) g; the concentration of the sodium periodate solution described in step one is 20 mM-30 mM; the concentration of the sodium acetate buffer solution described in step one is 50 mM-70 mM, and the pH is 4-5.

4. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that In step 1, the surfaces of both sides of the PVDF membrane are modified by vibration using a modified solution, specifically by the following steps: ① Place the PVDF membrane on the surface of the modified solution, so that one side of the PVDF membrane contacts the modified solution and the other side contacts the air, and then oscillate for 6h to 7h at room temperature and an oscillation speed of 120r / min to 150r / min to obtain a PVDF membrane with one side modified; ② Replace the modification solution and repeat step ① to treat the other side of the modified PVDF membrane, and finally wash and dry to obtain the SP-PDA@PVDF membrane.

5. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 4, characterized in that The PVDF membrane described in step 1 has a pore size of 0.22 μm to 0.45 μm and a thickness of 125 μm to 150 μm.

6. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that The mass ratio of rGO described in step 2 to ethanol is 1 g: (100-200) mL; the mass ratio of rGO described in step 2 to pyrrole is 1 g: (2-4) mL; the mass ratio of rGO described in step 2 to FeCl3 solution is 1 g: (30.3-35) mL; the concentration of FeCl3 solution described in step 2 is 1 mol / L-2 mol / L.

7. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that In step 2, rGO is added to ethanol and stirred for 30 to 60 minutes at a rotation speed of 20 to 50 r / min. Pyrrole is then added and ultrasonically treated for 5 to 10 minutes at an ultrasonic power of 100 to 120 W. FeCl3 solution is then added and reacted in an ice bath at a temperature of -5 to 0°C for 6 to 8 hours. Finally, the mixture is washed with 1 to 2 mol / L HCl and dried to obtain a PPy / rGO conductive polymer.

8. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that In step 3, the reaction is carried out in a closed nitrogen atmosphere at a temperature of 50°C to 65°C for 6h to 10h, the solution turns light brown, and then epichlorohydrin is added, and stirred for 48h to 72h in a closed nitrogen atmosphere, a temperature of 50°C to 65°C and a rotation speed of 30r / min to 50r / min.

9. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that The mass ratio of the PPy / rGO conductive polymer described in step 4 to the volume ratio of deionized water is 1 g: (100-150) mL; the mass ratio of the ion-imprinted polymer described in step 4 to the volume ratio of methanol is 1 g: (180-200) mL.

10. The method for preparing an ECH cross-linked lithium ion imprinted membrane with high adsorption performance according to claim 1, characterized in that The ultrasonic treatment described in step 4 is specifically carried out at a power of 50W to 120W for 5min to 25min; The freeze drying described in step 4 is specifically freeze drying at a temperature of -40°C to 2°C for 12h to 18h.